Candidate SNP Markers of Gender-Biased Autoimmune Complications of Monogenic Diseases Are Predicted by a Significant Change in the Affinity of TATA-Binding Protein for Human Gene Promoters - Ponomarenko, Mikhail P.; Arkova, Olga; Rasskazov, Dmitry; Ponomarenko, Petr; Savinkova, Ludmila; Kolchanov, Nikolay (Frontiers in Immunology, 2016)
Some variations of human genome (for example, single nucleotide polymorphisms [SNPs]) are markers of hereditary diseases and drug responses. Analysis of them can help to improve treatment. Computer-based analysis of millions of SNPs in the 1000 Genomes project makes a search for SNP markers more targeted. Here we combined two computer-based approaches: DNA sequence analysis and keyword search in databases. In the binding sites for TATA-binding protein (TBP) in human gene promoters, we found candidate SNP markers of gender-biased autoimmune diseases, including rs1143627 (cachexia in rheumatoid arthritis [double prevalence among women]); rs11557611 (demyelinating diseases [thrice more prevalent among young white women than among nonwhite individuals]); rs17231520 and rs569033466 (both: atherosclerosis comorbid with related diseases [double prevalence among women]); rs563763767 (Hughes syndrome-related thrombosis [lethal during pregnancy]); rs2814778 (autoimmune diseases [excluding multiple sclerosis and rheumatoid arthritis] underlying hypergammaglobulinemia in women); rs72661131 and rs562962093 (both: preterm delivery in pregnant diabetic women); and rs35518301, rs34166473, rs34500389, rs33981098, rs33980857, rs397509430, rs34598529, rs33931746, rs281864525, and rs63750953 (all: autoimmune diseases underlying hypergammaglobulinemia in women). Validation of these predicted candidate SNP markers using the clinical standards may advance personalized medicine.